Controllable wrinkling patterns on liquid crystal polymer film/substrate systems by laser illumination. (July 2019) - Zhao, Shichen; Xu, Fan; Fu, Chenbo; Huo, Yongzhong
Abstract: Smart soft materials, because of their mechanical flexibility and quick response to multi-physics stimuli, have drawn considerable attention over the past few years. Here, we present controllable wrinkling patterns of a liquid crystal polymer film attached on a soft substrate, controlled by laser illumination that holds unique optical characteristics of high coherence and irradiance. To analyze the mechanical response of liquid crystal polymer film/substrate systems under laser illumination, we develop a mathematical model by introducing laser-induced strain that has continuous Gaussian distribution, into the Föppl–von Kármán nonlinear plate theory. We explore effects of photo illumination areas and light-induced bending moments on pattern formation and selection, and discuss the inherent difference compared with uniform illumination. We find that the critical wrinkling strain is independent of laser decay distance, while pattern formation and pattern evolution are primarily determined by this parameter and the half width of laser irradiation. Novel wrinkling patterns, including horseshoe-shaped and spiral modes, are observed upon laser illumination. Furthermore, we provide phase diagrams on pattern selection and bifurcation diagrams on pattern evolution, which could quantitatively guide the effective design of multi-functional surfaces and precisely remote control of diverse surface morphology.